As brincadeiras e os jogos na educação infantil - Leite, Margarida Maria de Alacoque (2016)
This article presents the importance of the jokes and games in the process of teaching and learning in the Child Education. The choice of this theme occurred believing the jokes and games must to do part of the routine of the children in this teaching mode. This article intends to discuss about the direction associated to jokes and games by teachers of the Preschool II of Child Education at Escola Municipal 04 de Outubro in José da Penha – RN, emphasizing the contributions that the jokes and games can provide in the construction of the learning of the children. For data collect and information about the study object, it was applied an open questionnaire with six questions directed to teachers in Preschool II at mentioned school. For support the research of qualitative and descriptive base and to make the data analysis was used the ideas by Piaget (1975), Vygotsky (1988;1994), Wallon (1998), Kishimoto (2003), The Referencial Curricular Nacional para a Educação Infantil - RCNEI (1998), The Diretrizes Curriculares Nacionais para a Educação Infantil – DCNEI (2010), among others. Therefore, concludes that, the research is important, considering teachers and researchers have more a referential about the fundamentals that guide the jokes and games. It is essential the direction of jokes and games in the practice of classroom in the mentioned teaching mode, in the perspective of ensure referrals and or proposals that contribute to the construction of knowledge, as well as, the development of several capacities of the children.